MAKNA LEKSIKON KATZE DALAM PERIBAHASA DAN UNGKAPAN BAHASA JERMAN: ANALISIS LINGUAKULTUROLOGI - Senja Borgin (Jurnal SORA, 2019)
This study examines the use of word “cat” in the proverbs and the German expressions of Linguaculturology approach. The aims of the discussion are to identify the meaning of lexicon cat or Katze in proverbs and German expressions and also the relatios of the meaning of lexicon Katze in the German society. Data were obtained from DUDEN Redewendungen (2008) dictionary. Presentation of result of data analysis presented by using descriptive method. The results show there are 10 proverbs and the German expressions with the Katze’s lexicon. What arises from the use of lexicon Katze in the proverbs and expressions in German language is negative meaning.